A highly-active Zn0.58Co2.42O4 spinel oxide as a promising cathode for proton-conducting solid oxide fuel cells. Issue 48 (6th December 2022) - Xu, Yangsen; Gu, Yueyuan; Bi, Lei
Abstract : The highly-active and chemically stable Zn0.58 Co2.42 O4 cathode allows a record-high fuel cell performance for proton-conducting solid oxide fuel cells using spinel oxide cathodes. Abstract : Zn0.58 Co2.42 O4 (ZCO), which is a novel spinel oxide, has been proposed as a cathode material for proton-conducting solid oxide fuel cells (H-SOFCs) to explore the possibility of using spinel oxide cathodes for H-SOFCs. The high oxygen-ion and proton migration kinetics of ZCO, which first-principles calculations and experiments have demonstrated, allow the ZCO cell to show high cell performance without impairing the stability of the material. Further optimizing the cathode/electrolyte interface, by utilizing the relatively low melting point of ZCO, allows a record-high performance to be obtained for the ZCO cell compared with other SOFCs using a spinel oxide cathode.